Communities organizing to promote equity: engaging local communities in public health responses to health inequities exacerbated by COVID-19–protocol paper - Pacheco, Christina M.; Bridges, Kristina M.; Ellerbeck, Edward F.; Ablah, Elizabeth; Greiner, K. Allen; Chen, Yvonnes; Collie-Akers, Vicki; Ramírez, Mariana; LeMaster, Joseph W.; Sykes, Kevin; Parente, Daniel J.; Corriveau, Erin; et al. (Frontiers in Public Health, 2024)
Background The COVID-19 pandemic has disproportionately impacted rural and under-resourced urban communities in Kansas. The state’s response to COVID-19 has relied on a highly decentralized and underfunded public health system, with 100 local health departments in the state, few of which had prior experience engaging local community coalitions in a coordinated response to a public health crisis. Methods To improve the capacity for local community-driven responses to COVID-19 and other public health needs, the University of Kansas Medical Center, in partnership with the Kansas Department of Health and Environment, will launch Communities Organizing to Promote Equity (COPE) in 20 counties across Kansas. COPE will establish Local Health Equity Action Teams (LHEATs), coalitions comprised of community members and service providers, who work with COPE-hired community health workers (CHWs) recruited to represent the diversity of the communities they serve. CHWs in each county are tasked with addressing unmet social needs of residents and supporting their county’s LHEAT. LHEATs are charged with implementing strategies to improve social determinants of health in their county. Monthly, LHEATs and CHWs from all 20 counties will come together as part of a learning collaborative to share strategies, foster innovation, and engage in peer problem-solving. These efforts will be supported by a multilevel communications strategy that will increase awareness of COPE activities and resources at the local level and successes across the state. Our mixed methods evaluation design will assess the processes and impact of COPE activities as well as barriers and facilitators to implementation using aspects of both the Consolidated Framework for Implementation Research (CFIR) and Reach, Effectiveness, Adoption, Implementation and Maintenance (RE-AIM) models. Discussion This protocol is designed to expand community capacity to strategically partner with local public health and social service partners to prioritize and implement health equity efforts. COPE intentionally engages historically resilient communities and those living in underserved rural areas to inform pragmatic strategies to improve health equity.